Study of Cikadu Edutourism Value Chain as A Buffer Zone of Tanjung Lesung - Filda Rahmiati; Andi Ina Yustina (AIBPM Publisher, 2022)
This paper profoundly examines the tourism value chain for a strategic advantage. A descriptive method was conducted by surveys and in-depth interviews with stakeholders in Cikadu Edutourism, including businesses, SMEs, community people, academicians, and the media. The value chain components of edutourism value chain's development strategy were evaluated to construct a comprehensive chain. Our findings indicate that the proposed programs could give Cikadu Edutourism a competitive edge by enhancing the quality of life, increasing revenue as a product sold to visitors, and a range of other benefits.